2020
DOI: 10.11606/issn.1678-4456.bjvras.2020.168582
|View full text |Cite
|
Sign up to set email alerts
|

Hematological values for free-living great fruit-eating bats, Artibeus lituratus (Chiroptera: Phyllostomidae)

Abstract: It was provide a hematological profile of Artibeus lituratus (Phyllostomidae: Stenodermatinae). Animals were collected from October 2017 to February 2018 in an urban forest in the city of Rio de Janeiro, Southeastern Brazil. Males and females showed similar overall mean values for the parameters analyzed. Males had higher values for erythrocytes (RBC), hematocrit and basophils. Females had higher levels of eosinophils than males. The hematological values reported here will serve as reference for future researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…Present study agrees with (Kuzel, 2020) who reported that male great fruiteating bat (Artibeus lituratus) higher than female in WBC, RBC, HB, Neutrophil, Lymphocyte and monocytes but male Artibeus lituratus less female in Platelet count. And agree with (Olayemi et al, 2006) who reported that male African Fruit Bat (Eidolon Helvum) higher than female in RBC, HCT, HB, MCV, WBC, Neutrophil, Esinophil and monocyte.…”
Section: Resultssupporting
confidence: 92%
“…Present study agrees with (Kuzel, 2020) who reported that male great fruiteating bat (Artibeus lituratus) higher than female in WBC, RBC, HB, Neutrophil, Lymphocyte and monocytes but male Artibeus lituratus less female in Platelet count. And agree with (Olayemi et al, 2006) who reported that male African Fruit Bat (Eidolon Helvum) higher than female in RBC, HCT, HB, MCV, WBC, Neutrophil, Esinophil and monocyte.…”
Section: Resultssupporting
confidence: 92%
“…The most relevant results in the red blood cell count show some bats with decreases in hemoglobin, in addition all individuals presented some low erythrocyte indices from day 0 to day 21 after inoculation, there being a clear normochromic microcytic anemia in M2 on day 14 post-inoculation and M9 presented a marginal erythrocytosis on day 21 postinoculation. The most relevant results in the white blood cell count compared to the values given for Artibeus bats (4.7 ± 2.4 × 10 9 /L) (31-34) (Table 2). show leukocytosis with lymphocytosis and monocytosis in individuals M6 and M8, in addition to lymphocytosis in M9 and leukocytosis with lymphocytosis in M11.…”
Section: Resultsmentioning
confidence: 96%
“…Next, blood samples were divided for molecular and serological ZIKV detection and whole blood for complete blood count (CBC). The CBC was made in a VetScan HM5 device previously calibrated for Phyllostomid bat leucocytes using the reference previous reports (31-34). Differential counts WBC were made also in blood smears stained with Giemsa dye following standard protocols.…”
Section: Methodsmentioning
confidence: 99%